One for My Baby : A Novel - Parsons, Tony, 1953- (London Harper, 2011)
Alfie Budd found the perfect woman with whom to spend the rest of his life, and then lost her. He doesn't believe you get a second chance at love. Returning to the England he left behind during the brief, idyllic time of his marriage, Alfie finds the rest of his world collapsing around him. He takes comfort in a string of pointless, transient affairs with his students at Churchill's Language School, and he tries to learn Tai Chi from an old Chinese man, George Chang. Will Alfie ever find a family life as strong as the Changs'? Can he give up meaningless sex for a meaningful relationship? And how do you play it when the woman you like has a difficult child who is infatuated with a TV wrestler known as The Slab? Like his runaway bestseller, Man and Boy, Tony Parsons's new novel is full of laughter and tears, biting social comment and overwhelming emotion.
Keywords: Teachers